Auricular prosthesis retained with implants: A case report - Lazić Vojkan; Todorović Ana; Lazić Marko; Konstantinović Vitomir (Serbian Medical Society - Dental Section, Belgrade, 2021)
Maxillofacial defects create physical, emotional and mental problems for the patient. The task of surgical-prosthetic rehabilitation is to provide best possible functional and esthetic solution. The aim of this paper was to present a modern approach to auricular defect rehabilitation. A 24-year-old patient with a lack of the right ear lobe due to trauma was admitted for aesthetic rehabilitation. Implant-retained ear prosthesis was indicated. Three implants were placed into mastoid region of the temporal bone, and after the period of osseointegration, an individualized bar was attached to them for the retention of an auricular prosthesis made out of silicone. Prosthetic rehabilitation, in this case, achieved excellent retention and restored the appearance as well as self-confidence of the patient.